Advanced photoluminescent nanomaterials for targeted bioimaging of cancer cells - Tooba Mohammadi; Hadi Gheybalizadeh; Elaheh Rahimpour; Jafar Soleymani; Vahid Shafiei-Irannejad (Heliyon)
The investigation of changes in the membrane of cancer cells holds great potential for biomedical applications. Malignant cells exhibit overexpression of receptors, which can be used for targeted drug delivery, therapy, and bioimaging. Targeted bioimaging is one the most accurate imaging methods with a non-invasive nature, allowing for localization of the malignant cell without disrupting cellular integrity. Also, bioimaging has the potential to enhance the quality of established imaging techniques like magnetic resonance imaging (MRI). The utilization of nanoparticles in targeted bioimaging enhances the imaging quality and efficiency. Biocompatible nanoparticles can easily penetrate cell membranes, while they can be readily functionalized on their surfaces toward cell receptors. This study reviews reports on the application of new advanced photoluminescent materials for targeted bioimaging using the cell membrane receptors. Also, the limitations and advantages of the application of nanoparticles have been reviewed along with the clinical consideration of their uses in bioimaging.